The level of application of ethical standards in the profession of university education from the viewpoint of faculty members at the University of Tishreen Failed study in Lattakia city (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The goal of research is to identify level of application of ethical standards for the profession of university education from the viewpoint of the members of the teaching staff. And know the differences in the answers to the members of the teaching staff according to the research variables: (sex, academic rank, years of experience, academic specialization). And it adopted a researcher on the descriptive analytical method, and included the research sample (154) by an educational body in the faculties of Tishreen University for the academic year 2014/2015, was the application of a questionnaire composed of four areas: (professional performance, relationship with the students, relationship with the community, and relationship with his colleagues). Among the most prominent search results: The existence of the average of the members of the teaching staff in the application of ethical standards in the profession of university education level. Also there were no statistically significant differences between the average answers faculty members at the level of application of ethical standards for the profession of university education differences depending on the variables of (sex, academic rank, experience), and there are statistically significant according to faculty in favor of scientism faculties.